GVC Participation and Deep Integration in Brazil - Hollweg, Claire H.; Rocha, Nadia (World Bank, Washington, DC, 2018)
The production of export goods has become increasingly unbundled, and countries positioning to become more integrated in the global economy are increasingly looking toward global value chains. This paper uses the Organisation for Economic Co-operation and Development/World Trade Organization's Trade in Value Added Database to assess Brazil's current integration in global value chains. It uses a structural gravity model estimated with parts and components to analyze the scope for Brazil to increase global value chain–related trade. One avenue to raise participation in global value chains is through (deeper) preferential trade agreements, and to this end the paper characterizes the level of integration of Brazil's current preferential trade agreements. Brazil has witnessed high growth in total domestic value added embodied in gross exports since 1995, yet it exhibits lower international engagement in global value chains, but tends to be stronger as a seller than a buyer. Most of the participation on the selling side comes from indirect linkages with domestic input sectors, and services sectors have been important for growing the indirect value added in global value chain–oriented exports. A deep integration agenda focusing not only on border measures, but also on beyond-the-border measures, would help Brazil to maximize the benefits from participation in global value chains. Other than its natural partners, Brazil should integrate with countries where global value chains are taking place. New agreements signed by Brazil and Mercosur with other regional members such as the Pacific Alliance should also take into consideration provisions such as investment, competition policy, and intellectual property rights, which are demonstrated to be very important for integration in global value chains.